REVIEW: Noted: Old hands advise the new - Allan Lee (Asia Pacific Network, 2013)
Review of: Interviewing: A guide for journalists and writers, by Gail Sedorkin (2nd edition). Crows Nest, NSW: Allen & Unwin, 2011, 206 pp. ISBN 978-174237094.